Role of traditional healers in psychosocial support in caring for the orphans: A case of Dar-es Salaam City, Tanzania - Massila Mariam; Mbwambo Zakaria H; Kayombo Edmund J (BMC, 2005)
Abstract Orphans are an increasing problem in developing countries particularly in Africa; due to the HIV/AIDS pandemic; and needs collective effort in intervention processes by including all stakeholders right from the grass roots level. This paper attempts to present the role of traditional healers in psychosocial support for orphan children in Dar-es-Salaam City with special focus on those whose parents have died because of HIV/AIDS. Six traditional healers who were involved in taking care of orphans were visited at their "vilinge" (traditional clinics). In total they had 72 orphans, 31 being boys and 41 being girls with age range from 3 years to 19. It was learned that traditional healers, besides providing remedies for illnesses/diseases of orphans, they also provided other basic needs. Further, they even provided psychosocial support allowing children to cope with orphan hood life with ease. Traditional healers are living within communities at the grass roots level; and appear unnoticed hidden forces, which are involved in taking care of orphans. This role of traditional healers in taking care of orphans needs to be recognised and even scaling it up by empowering them both in financial terms and training in basic skills of psychosocial techniques in how to handle orphans, in order to reduce discrimination and stigmatisation in the communities where they live.